Sosialisasi Literasi AntiKorupsi Di MTS Al – Muttaqin Untuk Mencegah Tindak Pidana Korupsi - Mellyana Novianty; Rika Nirmala Sari; Della Mawarni; Saherianti Saherianti; Chika Permatasari; Salwa Rideli Lutfi; Alwan Syahrani; Ilham Hudi (Lembaga Pengembangan Kinerja Dosen, 2024)
The condition of corruption in Indonesia seems to require serious efforts starting from schools. Basic education, especially anti-corruption education, must be strengthened in schools. Students of MTS Al-Muttaqin must be educated about anti-corruption literacy through this community service. Three stages of the implementation plan were carried out. The preparation stage includes licensing, coordination, and socialization at MTS Al-Muttaqin. The second stage is implementation, which includes socialization and counseling. The third stage is evaluation and preparation of the MTS Al-Muttaqin report. The results of the community service show that students are able to prevent corruption by studying anti-corruption.